2012
DOI: 10.1103/physrevb.86.054521
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory for a ferromagnetic nanowire/superconductor heterostructure: Transport, fluctuations, and topological superconductivity

Abstract: Motivated by the recent experiment of Wang et al. [Nature Physics 6, 389 (2010)], who observed a highly unusual transport behavior of ferromagnetic Cobalt nanowires proximity-coupled to superconducting electrodes, we study proximity effect and temperature-dependent transport in such a mesoscopic hybrid structure. It is assumed that the asymmetry in the tunneling barrier gives rise to the Rashba spin-orbit-coupling in the barrier that enables induced p-wave superconductivity in the ferromagnet to exist. We firs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 85 publications
0
31
0
1
Order By: Relevance
“…On the other hand, the lack of inversion symmetry can also occur at the interface between two different materials inducing an interfacial SO coupling. [37][38][39][40][42][43][44][45] This might be the scenario in some of the structures used in the experiments on SFS junctions. It is not straightforward to estimate the strength of the SO coupling for a given hybrid interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the lack of inversion symmetry can also occur at the interface between two different materials inducing an interfacial SO coupling. [37][38][39][40][42][43][44][45] This might be the scenario in some of the structures used in the experiments on SFS junctions. It is not straightforward to estimate the strength of the SO coupling for a given hybrid interface.…”
Section: Discussionmentioning
confidence: 99%
“…34 A finite SO coupling can result from either an intrinsic property of materials without inversion symmetry 35 or from geometrical constraints such as low dimensional structures or interfaces between different materials. [36][37][38][39][40][42][43][44][45] Specifically, Ref. 34 presented a unified view of the singlet-triplet conversion which connects the magnetic inhomogeneous mechanism with the one based on SO coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence in the form of a weak and broad zero-bias peak seems to provide some support to this hypothesis [21]. Several theoretical calculations [14,[30][31][32][33] have shown that as a matter of principle Majorana modes can emerge in ferromagnetic wires in superconductors, as had been suggested in more mesoscopic geometries [11,12,34,35]. Motivated by earlier STM works [36,37], some of the theoretical works [13,33,38,39] have modeled the system to be a chain of magnetic atoms (i.e.…”
Section: Introductionmentioning
confidence: 86%
“…We now turn to the physical realization [8-10, 29-33, 40, 47] of TS in a ferromagnetic nanowire in contact with a bulk s-wave superconductor. We note that the minimal model for the ferromagnetic wire proximity-coupled to a superconductor [30,31,34], as used in [21], is formally the same as the corresponding semiconductor nanowire TS system introduced in [8][9][10]47] with the only constraint being that the spin-splitting is arising from intrinsic exchange splitting in the ferromagnetic system whereas it is induced as a Zeeman splitting by an externally applied magnetic field in the semiconductor case. This has already been pointed out by Dumitrescu et al [31].…”
Section: Substrate-induced Renormalization Of the Topological Wirementioning
confidence: 99%
“…Although progress has been made in the understanding magnetic nanostructured materials studies of magnetic semiconductors nanotubes and nanowires (NWs) are still at a nascent stage [5][6][7]. Ferromagnetic semiconductors NWs can bring interesting applications to future magnetic recording media and electronic devices.…”
Section: Introductionmentioning
confidence: 99%